Model Online Industrial Technology Programs - Raj L Desai (International Journal of Informatics and Communication Technology (IJ-ICT), 2022)
This paper outlines a proposal for serving working professionals in industry by offering them two programs of study to enhance their education and improve their job prospects. The programs were specifically designed to meet the needs of the manufacturing industry in Texas. The courses are proposed to be offered online because we expected working people to be interested in these programs. By offering courses online we can attract a new group of working students that are constrained by their jobs from being able to take regular courses